The phenomenon of magical treasure hunting as an example for the definition of religious norms in the 18th century - Michalke, Alissa (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2020)
The phenomenon of magical treasure hunting experienced a phase of high popularity in the Holy Roman Empire of German Nation in the early modern period. The applied magical practices were just one part of the wide magical spectrum of that time. In fact, many of them were closely connected to Catholic liturgy. This article will, based on a case study from Bamberg, examine whether or how Catholic doctrine was distinguished from those magical practices and by whom. Furthermore, it will analyse the attitude of clergy and secular people towards magic in order to gain hidden treasure. The study of magical treasure hunting illustrates exemplarily the fight against popular piety and superstition in the XVIIIth century.